Faith et al.’s (2011) “corroboration assessment” leads to verificationism - Farris, James S.; Carpenter, James M. (Zootaxa, 2012)
As Faith et al. (2011) present it, drawing conclusions from possibly conflicting sources of evidence can be facilitated by what those authors call corroboration assessment